Multidrug-resistant Klebsiella pneumoniae from clinical isolates at dr. Soeradji Tirtonegoro central hospital Klaten - Virawan, Handi; Nuryastuti, Titik; Nirwati, Hera (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Klebsiella pneumoniae is a Gram-negative bacterium that often causes nosocomial infections. Use of broad-spectrum antibiotics as an empiric therapy has contributed to increases of K. Pneumoniae strains that are resistant to antibiotics. Therefore, a test on antibiotic susceptibility of K. pneumoniae is needed as a guide in treating a definitive therapy. Objective: This study aimed to measure the percentages of multidrug-resistant (MDR) of K. pneumoniae and its susceptibility at dr. Soeradji Tirtonegoro Central Hospital, Klaten, Central Java in 2017. Methods: This study was a descriptive study using secondary data at the Clinical Microbiology Laboratorium of dr. Soeradji Tirtonegoro Central Hospital, Klaten. The K. pneumoniae was isolated from patients hospitalized in the hospital from January 1, 2017, to December 31 2017. Identifications of the K. pneumoniae were conducted by a colony morphology observation, a gram staining, and a biochemical test. The test of antibiotics susceptibility used Kirby-Bauer method based on Clinical and Laboratory Standards Institute (CLSI). The data were analyzed by univariate analysis. Results: In 2017, there were 213 K. pneumoniae isolates from various clinical samples. Among them, 122 isolates were MDR K. pneumoniae (57.28%). The majority of MDR K. pneumoniae were resistant to a wide range of antibiotics. The MDR K. pneumoniae had only a good sensitivity to meropenem (98.43%), amikacin (93.75%), nitrofurantoin (88.89%), and fosfomycin (88.89%). In contrast, all non-MDR K. pneumoniae had good sensitivity to all tested antibiotics, except to ampicillin. Conclusion: The percentage of MDR K. pneumoniae isolates at the dr. Soeradji Tirtonegoro Cental in 2017 was 57%. Meropenem and amikacin could be considered as empirical therapies to cure an MDR K. pneumoniae infection.